2022
DOI: 10.1016/j.psj.2021.101537
|View full text |Cite
|
Sign up to set email alerts
|

Fiber characteristics and meat quality of different muscular tissues from slow- and fast-growing broilers

Abstract: Chicken meat is an important source of high-quality animal protein. Its consumption continues to grow in both developed and developing countries. Muscle fiber characteristics are key determinants of meat quality and quantity. Skeletal muscle is a highly plastic tissue that is affected by breed differences and muscular tissues. However, studies regarding the effects of different breeds and muscular tissues on the fibers and meat quality traits in broilers are lacking. In this study, Ross 308 chickens (fast-grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 34 publications
5
42
1
2
Order By: Relevance
“…pH 15 and pH u decreased in breast muscle of line S chickens ( p > 0.05), while pH 15 and pH u in thigh muscle was significantly reduced ( p < 0.05). Weng et al found similar results in that L* improved significantly and a* was reduced in thigh muscle of fast-growth chickens, and breast and thigh muscles from fast-growth birds always showed a low pH [ 27 ].…”
Section: Discussionmentioning
confidence: 87%
“…pH 15 and pH u decreased in breast muscle of line S chickens ( p > 0.05), while pH 15 and pH u in thigh muscle was significantly reduced ( p < 0.05). Weng et al found similar results in that L* improved significantly and a* was reduced in thigh muscle of fast-growth chickens, and breast and thigh muscles from fast-growth birds always showed a low pH [ 27 ].…”
Section: Discussionmentioning
confidence: 87%
“…Namely, the Warner-Bratzler shear value of slowgrowing ISA Dual chickens was almost double that of fast-growing Ross 308 chickens and higher than that of medium-growing JA757 chickens (17.26 N vs 9.00 N vs 13.06 N, respectively). A high shear force value in slow-growing chickens was also observed by Chodova et al (2021a) and Weng et al (2022). These results can be explained by the fact that in older chickens, there is an increase in the content of intramuscular connective tissue, which leads to greater hardness of the meat.…”
Section: Meat Chemical Compositionmentioning
confidence: 65%
“…China is the most productive goose producer in the world, and high meat quality is a major attribute that influences consumer acceptance, which is especially important for the meat industry. Weng et al [ 20 ] indicated that with an increasing CSA, the pH of postmortem breast muscle decreased slowly, and the glycolysis potential of muscle decreased, which eventually led to an increase in the final pH of meat. Additionally, muscle with a larger fiber size exhibited lower drip loss values and a lighter meat color than muscle with a smaller fiber size [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%